UPAYA PENINGKATAN BERPIKIR KRITIS DAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MODEL PROBLEM BASED LEARNING (PBL) SISWA SEKOLAH DASAR - Wulandari, Dwi Astuti; Indarini, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to enhance and ezamine the critical thinking skills and learning outcomes of fourth-grade student at SD Kanisius Bedono through the Problem-Based Learning (PBL) model in the Pancasila Education subject. This research was conducted in two cycles, with each cycle consisting of two meetings. The observation students at SD Kanisius Bedono through the Problem-Based Learning (PBL) model in the Pancasila Education subject. This research was conducted in two cycles, with each cycle consisting of two meetings. The observations in the first cycle indicated that students' critical thinking skills were still in the low category, with an average score of 58, and only 12.5% of students were able to achieve the Minimum Mastery Criteria (KKTP). However, in the second cycle, there was an improvement, with the average critical thinking skill score increasing to 84.5%, and 95.8% of students successfully reaching the KKTP, due to a more structured implementation of the Problem-Based Learning (PBL) model in this cycle. The PBL model effectively encouraged students to actively engage in group discussions, identify and solve real-world problems, and exchange ideas with their classmates. This study highlights the importance of using innovative learning models to improve the quality of education, particularly in enhancing critical thinking skills at the elementary school level. The researcher hopes that schools will consistently implement the PBL model to provide students with a more meaningful and enjoyable learning experience.